If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7=n+3/6
We move all terms to the left:
7-(n+3/6)=0
We add all the numbers together, and all the variables
-(+n+3/6)+7=0
We get rid of parentheses
-n+7-3/6=0
We multiply all the terms by the denominator
-n*6-3+7*6=0
We add all the numbers together, and all the variables
-n*6+39=0
Wy multiply elements
-6n+39=0
We move all terms containing n to the left, all other terms to the right
-6n=-39
n=-39/-6
n=6+1/2
| 5x-7=2x+29 | | 4y-12=8y+54 | | x–17=–5 | | 6c-5=1/2; | | 4.6=0.6*x+0.4*5 | | 4x-1=54 | | -0.25n=136.75 | | 9u+13=-8(u-8) | | 3(u+5)=2u+4 | | 2/3z=5/6(2+z) | | 7(6-2i)=5(-3i+1 | | y=y+3/12 | | 3x-6=-18+x | | 0.5+c=-13.5+0.5c | | |4c-8|-3=25 | | 3x3−14x2+12x=0 | | 5x+6(-4x+16)=-56 | | 32x-24=12x+24 | | -6n+21=12n-15= | | 2x+21+3x+4=180 | | 3v-20=-32 | | 3r-r-7=r-7 | | 9x-5-1-2-8x7x1=0 | | 6(3x−7.2)=25.2 | | (3/5)x+4-(1/6)=1/10 | | 5b^2-9b=-4 | | 5v^2+20=80 | | 2y=8+8 | | -5n+3=18 | | x+7-8=14 | | 3x+6x-7x=-4 | | |x+7|-8=14 |